Swimming spatial-temporal variables obtained with manual timekeeping and video analysis: comparison, correlation, and agreement - De Souza Castro, F. A.; Zimermann, M.; Menin, L.; Nazário, C.; Pereira, G. A.; Fiori, J. M.; Guedes, J. P. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The aim of this study was to compare, correlate, and verify the concordance of stroke rate (SR), length (SL), and velocity (v) obtained with both manual stopwatch and with video analysis. Fifteen male masters swimmers (39.7±8.3 years old) performed a 2000-m front-crawl in a 25 m swimming pool. Along 10 m from four steps, three consecutive stroke cycles and time to cover 10 m were manually timed (Casio HS-30W, Japan) by four (4 years experienced) timekeepers (TK). At the same time, sagittal images were obtained with a video camera (60 Hz) and then digitalized (10 m calibration ruler). Comparison, intraclass correlation, and agreement analysis were applied (? = 0.05). No difference (p>0.05) was found for SR, SL and v in any step (overall SR, SL, and v, respectively manual and video results: 27.8±3.3 and 28.2±2.7 cycles.min-1; 2.29±0.3 and 2.26±0.3 m; 1.05±0.13 and 1.06±0.13 m.s-1). Results were highly correlated (intraclass correlation > 0.90), and showed agreement in all steps (bias for SR, SL, and v were, respectively, less than: 0.64 cycles.min-1; 0.04 m; and 0.01 m.s-1.